New Types of Continuities - İbrahim Çanak; Mehmet Dik (Abstract and Applied Analysis)
A new concept of quasi slowly oscillating continuity is introduced. Furthermore, it is shown that this kind of continuity implies ordinary continuity, but the converse is not always true.